2008
DOI: 10.1002/hep.22467
|View full text |Cite
|
Sign up to set email alerts
|

The hepatic apelin system

Abstract: Apelin is a peptide that plays an important role in heart physiology and pathophysiology, inflammation, and angiogenesis. We evaluated whether the endogenous apelin system is involved in the pathogenesis of the hepatic remodeling and cardiovascular and renal complications occurring in advanced liver disease. The circulating levels of apelin, the messenger RNA (mRNA) and protein expression of apelin and apelin receptor, the immunohistological detection of apelin and apelin receptor, and the effects induced by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
2
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(119 citation statements)
references
References 24 publications
5
106
2
6
Order By: Relevance
“…In brain tumours, the expression of apelin and APJ is up-regulated in microvascular proliferations (Kalin et al 2007), while tumour cell lines overexpressing apelin show increased growth (Sorli et al 2007). The pathophysiological effects of apelin in angiogenesis have also been reported for the liver, where the apelinergic system is a factor in portosystemic collaterisation and splanchnic neovascularisation in portal hypotensive rats (Tiani et al 2009) as well as in neovascularisation during liver cirrhosis (Principe et al 2008). However, apelin may have therapeutic effects in ischaemia recovery due to vessel regeneration and endothelial proliferation (Eyries et al 2008) and blood vessel diameter regulation (Kidoya et al 2010).…”
Section: Role Of Apelin/apj In Angiogenesismentioning
confidence: 99%
“…In brain tumours, the expression of apelin and APJ is up-regulated in microvascular proliferations (Kalin et al 2007), while tumour cell lines overexpressing apelin show increased growth (Sorli et al 2007). The pathophysiological effects of apelin in angiogenesis have also been reported for the liver, where the apelinergic system is a factor in portosystemic collaterisation and splanchnic neovascularisation in portal hypotensive rats (Tiani et al 2009) as well as in neovascularisation during liver cirrhosis (Principe et al 2008). However, apelin may have therapeutic effects in ischaemia recovery due to vessel regeneration and endothelial proliferation (Eyries et al 2008) and blood vessel diameter regulation (Kidoya et al 2010).…”
Section: Role Of Apelin/apj In Angiogenesismentioning
confidence: 99%
“…This adipokine represent the the endogenous ligand of the orphan G protein-coupled receptor APJ, and is known to display a pro-angiogenic role [74]. The interest in apelin, which is expressed and secreted by adipose tissue both in mice and humans [75], has been generated by a study reporting that its levels were markedly increased in cirrhotic liver [76]. Apelin was found to be highly expressed by HSCs and in the same study the use of an antagonist of the apelin receptor was reported to inhibit not only angiogenesis but also hepatic fibrosis.…”
Section: Adipokinesmentioning
confidence: 99%
“…The apelin system is proposed to have a role in pathophysiological angiogenesis, contributing to portosystemic collateralization and splanchnic neovascularization in portal hypertensive rats (Tiani et al, 2009), neoangiogenesis in liver cirrhosis (Principe et al, 2008), and tumor neoangiogenesis (Kä lin et al, 2007;Sorli et al, 2007). However, angiogenic effects (Eyries et al, 2008) and induction of larger nonleaky vessels by apelin (Kidoya et al, 2010) appear to be beneficial in recovery from ischemia.…”
Section: A Cardiovascular Diseasementioning
confidence: 99%